Numerical investigation on thermal-hydraulic characteristics of the micro heat sink with gradient distribution pin fin arrays and narrow slots. (5th February 2022) - Yan, Yunfei; Xue, Zongguo; Xu, Fulei; Li, Lixian; Shen, Kaiming; Li, Jianbo; Yang, Zhongqing; He, Ziqiang
Highlights: A gradient distribution with narrow slots heat sink and improved designs are proposed. Pressure drop of improved gradient distribution decreases by 28.7%–33.4%. Maximum wall temperature of improved structures decreases by 4.4 K–26.6 K. Heat transfer coefficient of improved structures increases by 11.9%–23.0% Abstract: Targeting at decreasing the pressure drop in the micro heat sink, a gradient distribution pin fin arrays and narrow slots (GPN) is proposed. In addition, in order to further reduce the pressure drop of the micro heat sink, three improved are proposed, including GPN48, GPN2244, GPN264 by changed the number and position distribution of the pin fin arrays in the narrow slots. The results show that the pressure drop of the three improved gradient distribution pin fin arrays and narrow slots decreases by 28.7%–33.4% at a certain volumetric flow rate ( Qv = 120 ml/min, Re = 563) when comparing with the conventional gradient distribution. Furthermore, when Re ranged from 188 to 1125, the maximum wall temperature of the three improved gradient distribution pin fin arrays and narrow slots decreases by 4.4 K–26.6 K when comparing with the gradient distribution (GPN). When the Re = 563, the heat flux limit of GPN is only 82 W/cm 2, while GPN48, GPN2244 and GPN264 reached 109 W/cm 2, 114 W/cm 2 and 120 W/cm 2 respectively. Especially, comparing with GPN, the average heat transfer coefficient of GPN48, GPN2244 and GPN264 increases by 11.9%–23.0% ( Re = 118), which greatly improves the application reliability in the micro heat sink.